Perancangan Aplikasi SIGAB pada Polresta Banjarmasin Berbasis Sistem Informasi Geografis Mobile Android - Muhammad Hidayat; Subandi, Subandi (Ikatan Ahli Informatika Indonesia, 2023)
This study presents the design and development of the SIGAB Application based on the Android Mobile Geographic Information System to support the Banjarmasin City Police in maintaining security, order, and public services. By utilizing Android mobile technology and basic maps using Google Maps. The SIGAB Application can be easily and quickly accessed by field officers. This allows them to respond to incidents more quickly and efficiently. Enterprise Architecture Planning (EAP) was chosen as the appropriate methodology for the development of the SIGAB Application. The EAP process involves seven blocks, each constructed through four stages: the Planning Initialization stage, the current condition assessment stage (business and system modeling, and current technology), the Future Enterprise Plan review stage (data architecture, application architecture, and technology architecture), and finally, the Implementation Plan stage, resulting in a Blueprint that can be used as a reference. The design of the SIGAB Application resulted in 9 database designs and 8 user interfaces for public access, 6 user interfaces for field personnel access, and 6 user interfaces for operator access at the Banjarmasin City Police. As of August 2023, the SIGAB Application has been used by 598 users with public access rights in Banjarmasin City and 774 users with access rights for members of the Banjarmasin City Police. The role of the SIGAB Application can optimize the operations of the Banjarmasin City Police and enhance the security of the Banjarmasin City area.